The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1021/ed044p356
|View full text |Cite
|
Sign up to set email alerts
|

Textbook errors index

Abstract: Lists errors found in chemistry textbooks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 1967, this Journal published a listing of 78 textbook errors with an abstract for each one, which was compiled from its published series "Textbook Errors" (1). Two decades later I found that about half of the errors were still committed in the then-current textbooks.…”
Section: Correction Of Textbook Errorsmentioning
confidence: 99%
“…In 1967, this Journal published a listing of 78 textbook errors with an abstract for each one, which was compiled from its published series "Textbook Errors" (1). Two decades later I found that about half of the errors were still committed in the then-current textbooks.…”
Section: Correction Of Textbook Errorsmentioning
confidence: 99%